Fossilized Jews and Witnessing Dinosaurs at the Creation Museum: Public Remembering and Forgetting at a Young Earth Creationist “Memory Place” - Nash, Dustin (Studies in Christian-Jewish Relations, 2019)
The Creation Museum (Petersburg, KY) embraces dinosaurs and their bones as witnesses to the historicity of the biblical creation narrative. While many have critiqued the institution’s presentation of the past, approaching this space as a memory place reveals previously unrecognized implications that its historical claims entail. In particular, expanding the place of dinosaurs within the Young Earth creationist memory of the past has compelled a parallel diminution in the representation of ancient and modern Jews in exhibits and related literature. In other words, having incorporated paleontology into its theological worldview, the Creation Museum is compelled to present Jews as quixotic fossils with no particular function in the divine plan for history. As the museum’s profile as a memory place for American evangelicals grows, this could undercut the theological foundations that have encouraged robust relations between that group and Jews over the past half-century.